2011
DOI: 10.1103/physrevb.84.054415
|View full text |Cite
|
Sign up to set email alerts
|

Theory of laser-induced ultrafast magneto-optic spin flip and transfer in charged two-magnetic-center molecular ions: Role of bridging atoms

Abstract: Laser-induced ultrafast spin manipulations in positively charged two-magnetic-center molecular ions with a small number of bridging atoms are investigated to explore the role of bridging atoms in the spin switching process and spin transferability between the magnetic centers via the Λ process. Taking O and Mg as examples for bridging atoms, fully ab initio calculations demonstrate that spin flip can be readily achieved on subpicosecond time scales at both magnetic centers of the linear structures composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
0
19
1
Order By: Relevance
“…Furthermore, this analytical model is capable of describing laser-induced spinflipping processes on magnetic materials with triplet ground state and strongly localized spin density. Such materials can comprise, among others, linear or branched metallic chains deposited on inert surfaces, [9][10][11] metallic clusters in the gas phase (with or without chromophores such as CO as experimental magnetic-state markers), 12 and ligand-stabilized complexes in solution. 13,14 For the time evolution of the system, we use a wave function rather than a density-matrix approach exploited by other authors (see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this analytical model is capable of describing laser-induced spinflipping processes on magnetic materials with triplet ground state and strongly localized spin density. Such materials can comprise, among others, linear or branched metallic chains deposited on inert surfaces, [9][10][11] metallic clusters in the gas phase (with or without chromophores such as CO as experimental magnetic-state markers), 12 and ligand-stabilized complexes in solution. 13,14 For the time evolution of the system, we use a wave function rather than a density-matrix approach exploited by other authors (see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In numerous ultrafast, laser-induced, magnetization-dynamics scenarios we have already demonstrated that Λ processes can act as exact microscopic spin-transition mechanisms on various bare and ligand-stabilized molecular systems [25]- [27]. In our previous studies we demonstrated that this theoretical model is also effective for the endohedral fullerenes [28], [29].…”
Section: Theory and Methodsmentioning
confidence: 89%
“…Our own codes are implemented in the last two steps for the computation of the SOC, the coupling to the static external magnetic field, the time propagation during the spin-switching processes, the optimization of the laser pulse (genetic algorithm), and the global search for the intermediate states involved in the ultrafast L process [22]. The step-by-step description of the equations and computational details can be found elsewhere [27,34].…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…have different local symmetry) [24]. We know that in the second case there is a much higher degree of spin-density localization, as investigated in our recent work [27], while in the first case, at least theoretically, both active centers will always carry an equal amount of spin density, rendering any spin-manipulating process nonlocal. At the same time we know that in order to induce a L process the states G 1 and G 2 need to be quasidegenerate.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation